The impact of home safety on sleep in a Latin American country - Simonelli, Guido (2015)
Objectives: We sought to assess the impact of feelings of safety in one's neighborhood and home on sleep quality and sleep duration. Design: The design is a cross-sectional survey using face-to-face interviews, as part of the Argentine Social Debt Observatory assessment. Setting: The setting is a nationwide data from Argentina. Participants: There are 5636 participants aged 18 years and older. Intervention (if any): N/A. Measurements: The relationships between both subjective sleep quality and self-reported sleep duration, categorized as short (b7 hours), normal (7-8 hours), and long (N8 hours)with safety in one's neighborhood and one's home,were analyzed. Age, sex, obesity, neighborhood socioeconomic status, and education were included as covariates. Results: Feeling unsafe in one's homewas strongly associatedwith poorer sleep quality andwith short sleep duration. Feeling unsafe in one's neighborhood was initially associated with reduced sleep quality but was no longer significant after controlling for home safety. In contrast, we found no correlation between safety measures and long sleep. In analyses stratified by sex, feeling unsafe in one's home was associated with poor sleep quality in women but not in men. Conclusions: Our findings suggest that safety in the home has an important effect on both sleep quality and duration, particularly among women. In contrast, after accounting for safety in the home, neighborhood safety does not impact sleep. Further research is warranted to identify mechanisms underlying the sex differences in susceptibility to poor sleep quality and shorter sleep duration, as well as to assess whether interventions addressing safety in the home can be used to improve sleep and overall health.